Early evidence on how Industry 4.0 reshapes MNEs’ global value chains: The role of value creation versus value capturing by headquarters and foreign subsidiaries - Lee, Jeoung Yul; Kim, Daekwan; Choi, Byungchul; Jiménez, Alfredo (Journal of International Business Studies, 2023)
In anticipation of the upcoming changes and turbulence caused by Industry 4.0, in which digital integration connects all value chain members, managers at leading multinational enterprises (MNEs) are scrambling to predict the associated changes in the market. This pioneering study advances our understanding by investigating the impact of an MNE’s Industry 4.0 orientation on the globalization of its value chain network. Identifying two types of value-generation activities as potential moderators, namely value creation and value capturing, we compare the moderation effects when these activities are conducted by headquarters versus foreign subsidiaries. We test the proposed model using a panel dataset comprising 5572 subsidiary-year observations from 358 Korean MNEs from 2011 to 2019. The results show that an MNE’s Industry 4.0 orientation leads to a more rapid expansion of its distribution network than of its supplier network. Furthermore, value creation by headquarters has a stronger positive impact on the globalization of its distribution network than that of its supplier network, whereas value creation by subsidiaries has a stronger positive impact on the globalization of its supplier network than that of its distribution network. However, value capturing has a stronger impact on the globalization of the MNE’s distribution network than that of its supplier network when performed by both locations. This study concludes by discussing the theoretical and managerial implications.